A new genus and two new species of Alysiinae (Hymenoptera: Braconidae) from Papua New Guinea - Braet, Yves; Achterberg, Cees Van (Zootaxa, 2014)
Two new species of the genus Leptotrema van Achterberg, 1988 and one new genus of the Alysiinae from Mt Wilhelm, Madang Province, Papua New Guinea are described and illustrated. The distribution of the genus Leptotrema is extended to the Australasian region. Three new combinations are established Idiasta fulmeki (Fischer, 2010) comb. n. (=Microcrasis fulmeki Fischer, 2010), Apiasta postfurcata (Papp, 1966) comb. n. (= Microcrasis postfurcata (Papp, 1966)), and Leptotrema. bovefemora (Bhat, 1979) comb. nov. (=Aspilota bovefemora Bhat, 1979). The status of the genus Apiasta Wharton, 2002 (stat. n.) is reviewed. Keys are provided to enable their identification.